Formation of silicon nanowires by chemical vapour deposition technique using indium catalyst / Chong Su Kong - Chong, Su Kong (2012)
Formations of silicon nanowires using aurum and indium catalyst by plasma-enhanced chemical vapour deposition and hot-wire chemical vapour deposition techniques were studied in this work. The depositions were carried out by using a home-built dual-mode plasma-assisted hot-wire chemical vapour deposition system. A tungsten filament with purity of 99.95% was employed for evaporation of aurum or indium wire to form catalyst on a substrate. Silane gas, which was diluted in hydrogen carrier gas was used as a precursor for the growth of the silicon nanowires. Plasma was generated through a power electrode by a radio frequency generator (13.56 MHz), and hot-wire process was initiated by heating the same tungsten filament used for evaporation. Indium catalyst showed better catalytic effect compared to aurum catalyst for low temperature growth of silicon nanowires. Under the same deposition conditions, aurum catalyst was only able to induce short worm-like nanowires with length ~0.9 μm. Indium catalyst, however, induced higher density of worm-like nanowires with length up to 10 μm. The results showed that the alignment of the nanowires is very dependent on the catalyst size. Large catalyst size tends to induce randomly-oriented worm-like nanowires, while aligned nanowires can be formed by reducing the catalyst size to ≤ 137 nm. Plasma discharging silane gas created high energetic precursors for the growth of nanowires. As a result, higher radio frequency power produced higher density of nanowires (provided the critical power for nanowire growth is not exceeded). However, crystallinity of the nanowires showed an adverse effect with the radio frequency power, as the energetic ions bombardment can destroy the crystalline structures of the nanowires. Hot-wire chemical vapour deposition is promising for the production of high crystallinity of nanowires due to its ion-free process. The crystallinity of the nanowires was increased with increase in filament temperature. A threshold filament temperature for the growth of silicon nanowires was observed between 1400 and 1500oC. The whisker-like silicon nanowires started to form at filament temperature 1500oC. Further increase in filament temperature can increase the aspect ratio and decrease the kinked structure of the nanowires. High silane decomposition rate of hot-wire chemical vapour deposition could produce large quantities of silyl radicals for the catalytic growth of nanowires. The uncatalyzed silyl radicals tend to absorb onto the walls of the nanowires and result in the radial growth process. Radial growth of slanting columnar silicon nanocrystallite structures were observed on the nanowires. This contributed to the tapering of the nanowires. The axial and radial growth mechanisms of the indium catalyzed silicon nanowires were studied by varying the deposition time. The axial and radial growth rates of ~280 ± 60 and ~12.0 ± 0.1 nm/min were obtained. The axial and radial growth processes resulted in the formation of crystalline silicon/slanting silicon nanocolumns core-shell nanowires with aspect ratio of ~18 ± 2.